INTERNATIONAL FINANCIAL REPORTING STANDARDS ADOPTION, INVESTOR PROTECTION, AND FOREIGN PORTFOLIO INVESTMENT: A REVIEW - Shovon, Md. Kamrul Hasan (International Journal of Accounting & Finance Review, 2021)
This paper aims to analyze the impacts of International Financial Reporting Standards (IFRS) adoption on foreign portfolio investment (FPI) in relation to investor protection based on existing empirical literature. This study uses a historical approach and focuses on thirty-six relevant articles published in accounting and finance journals. The author provides a theoretical groundwork of the association between IFRS adoption and FPI and summarizes the results. The findings are critically analyzed by employing developed vs. developing country lens. The review study reveals that the effects of IFRS adoption on FPI significantly differ between developed and developing countries. Although the positive impact of IFRS adoption on FPI is documented in existing literature, not all countries (particularly developing countries), firms, and users have benefited or equally benefited from IFRS adoption regarding FPI. In addition, the positive impacts of IFRS adoption on FPI are associated with the country's regulatory environment, such as level of investor protection. The findings of the study suggest that developing countries should ensure a proper regulatory environment to reap the full benefits of IFRS adoption. This review contributes to the existing literature by providing a comparative analysis of IFRS adoption effect on FPI between developed and developing countries while also suggests future research avenues.JEL Classification Codes: M41, Z23, B17.